Ethnomathematics Study In Tobacco Farming Mathematics in Balung Sub-District, Jember District - Qomaria, Laela; Putra, Eric Dwi; Panglipur, Indah Rahayu (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
Ethnomathematics is the science that relates how mathematics in culture and there is a relationship between mathematics and culture. The purpose of this study was to determine the traditional calculations that are contained in tobacco farming activities. This research uses descriptive research type with an ethnographic approach. The research subjects were tobacco farmers in Balung District, Jember Regency. The data collection methods used were interviews and documentation. This data collection process aims to identify and document the ethnomathematics applied by farmers in tobacco farming activities. Data analysis was conducted using a descriptive approach to describe and understand the application of ethnomathematics concepts in the context of tobacco farming. Through interviews with tobacco farmers, it was found that tobacco farmers' activities involve aspects of mathematics, namely counting, measuring and calculating.